Unintended errors in the work of financial intermediaries: A comparative view between Islamic jurisprudence and the Saudi system - Obaida bin Moaz Al-Shaqfah, (International Journal of Law Research and Studies, 2025)
This research examines the unintentional errors of financial intermediaries in the Saudi market through a comparative study between Islamic jurisprudence and Saudi regulations. It aims to highlight the nature of these errors, their types, and the criteria for determining them. It also aims to analyze their effects on contracts and financial transactions and associated compensation mechanisms.The research reviews the legal and jurisprudential framework for dealing with these errors, focusing on the position of the Saudi system and its jurisprudential adaptation, and cases of exemption from liability. It discusses clients' rights and financial intermediary obligations in cases of unintentional error, addressing investor protection mechanisms and preventive measures to prevent these errors.The significance of the research lies in providing an integrated framework for dealing with unintentional errors in financial intermediation, focusing on due compensation and assessment methods, and legal and jurisprudential protection for investors. The research concludes with findings and recommendations aimed at developing professional practices in financial intermediation, enhancing financial stability, and protecting the rights of market participants.
Keywords: Financial Intermediary; Unintentional Errors; Legal Liability; Financial Market; Investor Protection; Compensation Mechanisms; Saudi Financial Market; Islamic Jurisprudence